2009
DOI: 10.1086/596707
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Meningococcal Disease Associated with Genomic Bacterial Load

Abstract: In meningococcal disease, bacterial load is associated with likelihood of death, development of permanent disease sequelae, and prolonged hospitalization. The bacterial load was relatively higher in patients infected with N. meningitidis serogroup C than in those infected with other serogroups. The effects of age and IL-1 genotype on mortality are independent of a high genomic bacterial load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 34 publications
6
69
1
Order By: Relevance
“…We could not correlate DBL with mortality because none of our children died. Our data are in accordance with previous reports showing a relationship between DBL and worse outcome [34,10 ] and prolonged length of hospital stay [9] in patients with severe pneumococcal infections such as pneumonia and meningitis; as well as occurred in patients with meningococcal meningitis in whom there was an association between bacterial load and mortality, complications, sequelae and length of hospital stay [35].…”
Section: P=04)supporting
confidence: 93%
“…We could not correlate DBL with mortality because none of our children died. Our data are in accordance with previous reports showing a relationship between DBL and worse outcome [34,10 ] and prolonged length of hospital stay [9] in patients with severe pneumococcal infections such as pneumonia and meningitis; as well as occurred in patients with meningococcal meningitis in whom there was an association between bacterial load and mortality, complications, sequelae and length of hospital stay [35].…”
Section: P=04)supporting
confidence: 93%
“…This estimate of the bacterial DNA load in patient specimens may have clinical utility. Several studies have demonstrated that bacterial load measured by PCR correlates with disease severity and that the bacterial load is predictive of which patients are likely to become severely ill (35,37,41,42,52,53). Two studies independently identified a bacterial load of 1 ϫ 10 3 genome copies per ml of blood as a critical threshold above which patients had an increased risk of developing septic shock with E. coli (37), S. aureus (37), or Streptococcus pneumoniae (42), suggesting that quantitative measurement of the bacterial DNA load in blood may have clinical value.…”
Section: Discussionmentioning
confidence: 99%
“…In order to estimate the true concentration of pathogen DNA available in whole blood for molecular analysis from patients with bloodstream infections, we analyzed the data available in the literature. Organism-specific quantitative PCR has been used to measure the bacterial DNA present in whole-blood specimens from patients with sepsis, pneumonia, or suspected bloodstream infections (13,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Each of these studies analyzed whole-blood specimens from patients with suspected or confirmed infections rather than spiked samples for which the genome-to-viable cell ratio is expected to be close to 1:1.…”
Section: Repeated Analytical Testing By Pcr/esi-msmentioning
confidence: 99%
“…Moreover, heparin is not known to alter gene expression in Neisseria. Bacterial loads in patients with fulminant disease can reach up to 10 9 bacteria/ml (9,17,44). In order to prepare the inoculum for use in blood, N. meningitidis was grown overnight on GC agar plates and cultured in GC broth to early exponential phase (optical density [OD], 0.5 to 0.6).…”
Section: Methodsmentioning
confidence: 99%